A Comparison of the Chemical Composition, In Vitro Bioaccessibility and Antioxidant Activity of Phenolic Compounds from Rice Bran and Its Dietary Fibres - Zhao, Guanghe (Molecules, 2018)
The composition, in vitro bioaccessibility and antioxidant activities of the phenolic compounds in defatted rice bran (DRB) and its soluble and insoluble dietary fibres were systematically evaluated in this study. The total phenolic content of insoluble dietary fibre from DRB (IDFDRB) was much higher than that of the soluble dietary fibre from DRB (SDFDRB) but was 10% lower than that of DRB. Bound phenolics accounted for more than 90% of the total phenolics in IDFDRB, whereas they accounted for 34.2% and 40.5% of the total phenolics in DRB and SDFDRB, respectively. Additionally, the phenolic profiles and antioxidant activities were significantly different in DRB, SDFDRB and IDFDRB. The phenolic compounds in IDFDRB were much less bioaccessibility than those in DRB and SDFDRB due to the higher proportion of bound phenolics in IDFDRB. Considering that bound phenolics could be released from food matrices by bacterial enzymes in the large intestine and go on to exert significant beneficial health effects in vivo, further studies on IDFDRB are needed to investigate the release of the phenolics from IDFDRB via gut microbiota and the related health benefits.